The Effects of Self-Efficacy on Students’ Reading Comprehension - M, Andi Ikhsan Anggriawan; Jabu, Baso; Dollah, Syarifuddin (Celebes Journal of Language Studies, 2023)
Self-efficacy is concerned with people’s beliefs in their capabilities to do something including reading. Reading comprehension is a part of English study measuring understanding of English. The objectives of this research were (1) to investigate the students’ self-efficacy in reading comprehension (2) to investigate the students’ reading comprehension and (3) to investigate whether there are the effects of students’ self-efficacy on their reading comprehension. This research applied Ex Post Facto. The sample of 33 students was selected by using the cluster random sampling technique. Data collection used reading tests and questionnaires. The data were analyzed by using SPSS 23. The result showed that the percentage of the students’ self-efficacy was in the high category, and the students’ reading comprehension was in the good category. There was no effect of self-efficacy on reading comprehension in this research.